Implication of IL-2/IL-21 region in systemic sclerosis genetic susceptibility. Issue 7 (21st November 2012) - Diaz-Gallo, Lina-Marcela; Simeon, Carmen P; Broen, Jasper C; Ortego-Centeno, Norberto; Beretta, Lorenzo; Vonk, Madelon C; Carreira, Patricia E; Vargas, Sofia; Román-Ivorra, José Andrés; González-Gay, Miguel A; Tolosa, Carlos; López-Longo, Francisco Javier; et al.
Abstract : Objective: The interleukin 2 ( IL-2 ) and interleukin 21 ( IL-21) locus at chromosome 4q27 has been associated with several autoimmune diseases, and both genes are related to immune system functions. The aim of this study was to evaluate the role of the IL-2/IL-21 locus in systemic sclerosis (SSc). Patients and methods: The case control study included 4493 SSc Caucasian patients and 5856 healthy controls from eight Caucasian populations (Spain, Germany, The Netherlands, USA, Italy, Sweden, UK and Norway). Four single nucleotide polymorphisms (rs2069762, rs6822844, rs6835457 and rs907715) were genotyped using TaqMan allelic discrimination assays. Results: We observed evidence of association of the rs6822844 and rs907715 variants with global SSc (pc =6.6E-4 and pc =7.2E-3, respectively). Similar statistically significant associations were observed for the limited cutaneous form of the disease. The conditional regression analysis suggested that the most likely genetic variation responsible for the association was the rs6822844 polymorphism. Consistently, the rs2069762A-rs6822844T-rs6835457G-rs907715T allelic combination showed evidence of association with SSc and limited cutaneous SSc subtype (pc =1.7E-03 and pc =8E-4, respectively). Conclusions: These results suggested that the IL-2/IL-21 locus influences the genetic susceptibility to SSc. Moreover, this study provided further support for the IL-2/IL-21 locus as a common genetic factor in autoimmune diseases.